Achieving Complete Nasal Lining Closure at Primary Cleft Palate Repair When the Lesser Segments Have Collapsed. (December 2021) - Calis, Mert; Tse, Raymond W.
Obtaining a tension-free 2-layer anatomic closure at cleft palate repair reduces risks of fistula and facilitates later alveolar bone grafting. Anterior nasal lining closure can be one of the most challenging aspects of repair but is rarely discussed. We present our approach to palatoplasty for BCLP and additional technical maneuvers for closure in the unfavorable configuration when the lesser segments are collapsed against the vomer: "inside-out" approach along the cleft margin provides access for accurate incision; elevation of medial pterygoid mucoperiosteum provides access further anteriorly to separate nasal lining from palatal shelf; mobilization of lining off of bone when 2 structures are in apposition opens a space for access; nasal lining can be drawn into view with a hook; and the nasal lining closure can be passed back through the space to heal in an anatomic relationship, cephalic to the bony shelves.